2015
DOI: 10.1063/1.4916542
|View full text |Cite
|
Sign up to set email alerts
|

Thermally activated coercivity in core-shell permanent magnets

Abstract: Finite element micromagnetic simulations are used to compute the temperature-dependent hysteresis properties of Nd2Fe14B permanent magnets in order to assess the influence of a hard (Dy,Nd)2Fe14B shell. The simulations show that the 4 nm thick shell cancels out the reduction in coercivity from an outer defect layer, which is known to exist at the grain boundaries in NdFeB permanent magnets. Activation volumes are computed and shown to depend on the structure's configuration as well as the temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 25 publications
1
22
0
1
Order By: Relevance
“…This discrepancy was recently overcome by introducing a nucleus at the surface of the polycrystalline model 25) . In addition, thermal uctuations can further reduce the coercivity, ~15% for room temperature calculations as reported by Bance et al 26,27) , which was not taken into account in this simulation by Sepehri-Amin et al 23) . In the Nd-Fe-B sintered magnets, the surface grains have almost no coercivity due to the defects created during surface machining/polishing or surface oxidation and the magnetization of the surface grains reverse at a lower magnetic eld than the nucleation eld 28) .…”
Section: Effect Of Grain Size On Coercivity and Thermal Stability Of mentioning
confidence: 68%
“…This discrepancy was recently overcome by introducing a nucleus at the surface of the polycrystalline model 25) . In addition, thermal uctuations can further reduce the coercivity, ~15% for room temperature calculations as reported by Bance et al 26,27) , which was not taken into account in this simulation by Sepehri-Amin et al 23) . In the Nd-Fe-B sintered magnets, the surface grains have almost no coercivity due to the defects created during surface machining/polishing or surface oxidation and the magnetization of the surface grains reverse at a lower magnetic eld than the nucleation eld 28) .…”
Section: Effect Of Grain Size On Coercivity and Thermal Stability Of mentioning
confidence: 68%
“…The temperature dependence of coercivity is generally due to two factors: the temperature-dependent magnetocrystalline anisotropy and the thermal fluctuations at finite temperatures. Bance et al considered both of these two factors in their micromagnetic simulations and found that thermal fluctuations can reduce the coercivity by 15% at room temperature and by 25% at 450 K. 25,26 Here, the grain shape is the focus and the thermal fluctuations are ignored. We take the temperature dependent magnetocrystalline anisotropy and saturation magnetization 37 to simulate the temperature dependence of coercivity, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, to the best of our knowledge, a systematic study on the grain shape effect in Nd-Fe-B is still meaningful according to the literatures. Bance et al [25][26][27] used the cubic or dodecahedral single grain covered by a defect layer to study the defect thickness dependent angular dependence of coercivity and the thermally activated coercivity in Nd-Fe-B by micromagnetic simulations. Based on the sub-micron Nd 2 Fe 14 B single and perfect grain with a rectangular prism shape, Thielsch et al 23 applied micromagnetic simulations to reveal the dependence of coercivity on length ratios.…”
Section: Introductionmentioning
confidence: 99%
“…For Nd-Fe-B thin film models an activation volume of 200e800 nm 3 was determined, which correspond to a spherical activation radius of 3.63e5.76 nm [43]. Micromagnetic simulations further demonstrate, that a 4 nm thick (Dy 47 ,Nd 53 ) 2 Fe 14 B shell is sufficient to compensate the deterioration in coercivity due to a 2 nm thick soft magnetic defect zone [48].…”
Section: Discussionmentioning
confidence: 99%